Impact of Human Settlements on the Forests of Keran Valley Kashmir Himalayas, India - Haq, Shiekh Marifatul; Rashid, Irfan; Khuroo, Anzar A.; Lone, Javaid Fayaz; Gairola, Sumeet (Indian Forester, 2019)
The present study was aimed to study the impact of human settlements on forests of Karen valley in Kashmir Himalayas. Forest composition, community structure and diversity patterns are important ecological attributes significantly correlated with prevailing environmental as well as anthropogenic variables.The conversion of forest land for agriculture practices, grazing and pastures in the settlements has been especially accentuated in traditional settlements. Rapid rate of deforestation and disturbed patterns were indicated by a stem/stump ratio of 1.7. The density was low at the HD site with a tree density of 180ha-1. Human population is much dependent on forest resources for fuel and timber requirements. Due to poor socio-economic status, climatic severity and absence of alternate energy resources people are forced to rely on local forests resources. Our study revealed that the deforestation spreads faster near the human settlements and have a direct impact on the forest ecosystem. The results of present study may provide a baseline information for formulating conservation and management strategies for these and other adjoining forests.